Impact of teleconsultation on subsequent disease activity and flares in patients with systemic lupus erythematosus. (23rd September 2021) - Au Eong, Jonathan T W; Lateef, Aisha; Liang, Shen; Lim, Sandy H H; Tay, Sen Hee; Mak, Anselm; Cho, Jiacai
Abstract: Objectives: Despite the widespread adoption of teleconsultations amid the COVID-19 pandemic, their safety in SLE patients has not been evaluated. Here, we examined subsequent disease activity and flares among SLE patients who received teleconsultation vs in-person consultation. To discern differences in physicians' prescription behaviour during both forms of consultations, we compared corticosteroid dose adjustments. Methods: We studied adult SLE patients who were seen between 1 February 2020 and 1 February 2021. At each patient-visit, rheumatologists utilized phone/video teleconsultation or physical consultation at their discretion. Disease activity was assessed with SLE Disease Activity Index 2000 (SLEDAI-2K) and flares were defined by the SELENA-SLEDAI Flare Index (SFI). We derived a propensity score for patients who were chosen for physical consultation. Multivariable generalized estimation equations were used to analyse SLEDAI-2k and flare at the next visit, adjusted for the propensity score. Results: A total of 435 visits were recorded, of which 343 (78.9%) were physical visits and 92 (21.1%) were teleconsultations. The modality of consultation did not predict flare [OR for physical consultation (95% CI) 0.42 (0.04, 5.04), P =0.49] or SLEDAI-2k at the next visit [estimate of coefficient for physical consultation (95% CI) −0.19 (−0.80, 0.43), P =0.55]. Adjustments of prednisolone dosages were comparable between the two forms of visits [OR for physical consultation (95% CI) 1.34 (0.77, 2.34), P =0.30]. Conclusion: SLE disease activity and flares at the subsequent visit were similar between teleconsultations and physical consultations. Medication prescription behaviour, determined using adjustment in corticosteroid dosages, was not different between the two forms of visits.